Atividades experimentais em Física para o Ensino Médio em articulação com a BNCC com mediação não presencial no cenário da pandemia - Gottardi, Thiago Rodrigues (2023)
This work describes the construction of a methodology for addressing experimental activities in Physics for first-year high school students, in the context of Non-Face-toFace Pedagogical Activities (APNP) demanded by the context of the Coronavirus pandemic and based on general competencies of the Common National Curriculum Base, namely Knowledge, Scientific, Critical and Creative Thinking, Communication and Argumentation. The study was developed in two classes of the 1st year of high school, respectively, with 46 and 38 students, belonging to the Instituto Federal do Espírito Santo (IFES). One of the motivations of development was the need for and importance of the presence of experimental activities during the school year, even in the pandemic-imposed regime. Another motivation was the arrival of BNCC in 1st grade of high school and its implications in teaching practice. To this end, a sequence of actions was delineated that would enable students to perform experimental activities without teacher mediation, at home and consciously and reflexively. Therefore, two Workshops and four Experiments were developed using Diagram V as a structuring element and enabler of conceptual, practical and cognitive expressions. As data collection elements we use logbook, extra class calls, and Diagram V. Data analysis provided clues in the direction of achieving the proposed objective and allows a comparison with face-to-face proposals. Finally, the balance was that this work contributed to the training and inclusion of students and that the methodology used was effective.